INTERNATIONAL MARKETING IN THE SYSTEM OF FOREIGN TRADE MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The modern development of foreign economic activity of enterprises is characterized by the dynamic development of the world economy, which is based on international marketing. Effective management of foreign economic activity of enterprises is the most important factor in expanding market opportunities and potential segments in the international market..The purpose of the article. The purpose of the article is to find optimization solutions related to the formation of a new high-quality mechanism for managing international marketing to enable international business entities to successfully compete in the world market. The tasks of the article are to optimize methodological and methodical aspects and to create a mechanism for the formation of international marketing in the system of management of foreign trade activityMetods. The formation of an international marketing management system involves the use of advanced methods of analyzing market conditions, forecasting the development of global markets, and developing effective marketing strategies.Results. The article proves that the development of modern business is impossible without taking into account global trends and active participation in international markets. It is substantiated that it becomes important to form a set of marketing strategies. The activation of individual components of the international marketing complex forms a strategy that is focused on long-term success and development, taking into account the specifics of each market and the needs of the target audience. A mechanism for the formation of international marketing in the system of management of foreign trade activity has been built, taking into account the maximum factors that affect its effectiveness. It has been proved that the mechanism plays an important role in coordinating and optimizing all marketing activities aimed at achieving the company's strategic goals.Conclusiоns. The effectiveness of the formation of international marketing in the system of foreign trade management significantly affects the success of not only marketing activities, but also the overall productivity and efficiency of enterprises. This will allow enterprises to adapt to the requirements of the international market, attract and retain customers, reduce costs and increase efficiency.
Keywords: international marketing, international marketing management system, mechanism of formation of international marketing in the system of foreign trade management.